PENGARUH HARGA, PEMASARAN DIGITAL, DAN KUALITAS PELAYANAN TERHADAP PURCHASE INTENTION GALERI UMKM PERUMDA BIDADARI LABUAN BAJO - Peong, Hersanius Kurnia; Ciptosari, Fitri; Golwi, Trivonia; Haba, Paulus; Harvano, Yonas F; Syahrul, Syahrul (Journal of Management Small and Medium Enterprises (SMEs), 2024)
This study explores the impact of price, digital marketing, and service quality on consumer Purchase Intention at Perumda Bidadari MSME Gallery. The population involved all visitors with a sample of 100 respondents selected through the non-probability sampling method, using accidental sampling. Data collection using questionnaires. This research applies a quantitative approach to evaluate the relationship between variables. The research instrument was tested with validity and reliability. Statistical analysis uses t-test, f-test, normality test, multicollinearity, and linearity test. Data analysis using multiple linear regression. The results showed that service quality has a positive and significant impact on Purchase Intention, while the effect of price and digital marketing strategy is not significant. With an R Square value of 0.814, it shows that about 81.4% of the variation in Purchase Intention can be explained by the combination of price, digital marketing, and service quality factors. Keywords: Price; Digital Marketing; Service Quality; Purchase Intention